The Impact of Internal Energy Consumption on Efficiency and Emissions in Maritime Transport - Elma, Onur; Kaymakçı, Özgür Turay; Mercan, Hasan (Bursa Teknik Üniversitesi, 2025)
Maritime transportation plays a crucial role in moving passengers, vehicles, and freight. However, emissions from this sector have become a focus of environmental concerns. Therefore, accurate analysis is important to reduce ship emissions and develop more efficient solutions. The study investigates the energy usage and emissions of a ferry, which is an example of analyzing the impact of internal energy consumption on efficiency and emissions in maritime transport. The analysis concentrates on the fuel consumption of the gen-set. Although the main engine is responsible for most of the ferry's emissions, the gen-set, running at an average load of 37.5%, also significantly contributes to emissions. By using emission factors for pollutants such as CO2, NOx, SOx, CO, and PM, the study calculated the emissions from both the main engine and the gen-set. The results show that the gen-set is accountable for 10% of the total emissions despite its lower load. These points to the potential for enhancing electrical energy efficiency on board, primarily through load optimization, gen-set modernization, and waste heat recovery. By implementing these strategies, the ferry can decrease fuel consumption, reduce emissions, and transition to a more sustainable and environmentally friendly operation. The findings underscore the importance of focusing on the ferry's electrical energy efficiency to minimize its overall environmental impact.
FBA-2023-4192
Keywords: Electrical Engineering (Other); Elektrik Mühendisliği (Diğer) [EN] Mechatronics Engineering; Mekatronik Mühendisliği